2023
DOI: 10.1002/adma.202210994
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Wavelength Light‐Responsive Metal–Phenolic Network‐Based Microrobots for Reactive Species Scavenging

Abstract: Light‐driven microrobots with different propulsion mechanisms have attracted great attention in microrobot synthesis and applications. However, current systems rely heavily on precious metals, using a complex synthesis process and limited working wavelength. It is therefore of great interest to fabricate microrobots that can be driven by multi‐wavelength irradiation and with simple components. Here, metal–phenolic network (MPN)‐based microrobots are synthesized using a sacrificial polystyrene bead template and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…To verify that QC-derived QCN or TQCN retained the above properties, both formed stable nanocomplexes with Fe 2+ /Fe 3+ , and their absorption spectra showed a decrease in characteristic absorbance of QC at 372 nm and the appearance of a characteristic peak of iron ions at 300 nm, accompanied by similar solution color changes (Figure d,e and Figure S5). Subsequently, X-ray photoelectron spectroscopy (XPS) was detected to further clarify the electronic states of nanocomplexes formed by QCN and TQCN chelating free iron. , The high-resolution XPS spectra showed that the main peaks around 711.7 and 725 eV in the QCN/Fe 3+ nanocomplex and 712.5 and 725.3 eV in the TQCN/Fe 3+ nanocomplex were all assigned to Fe 2p 3/2 and Fe 2p 1/2 (Figure f,g and Figure S6), confirming the successful coordination of iron ions with QC molecules, not affected by TPP modification.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…To verify that QC-derived QCN or TQCN retained the above properties, both formed stable nanocomplexes with Fe 2+ /Fe 3+ , and their absorption spectra showed a decrease in characteristic absorbance of QC at 372 nm and the appearance of a characteristic peak of iron ions at 300 nm, accompanied by similar solution color changes (Figure d,e and Figure S5). Subsequently, X-ray photoelectron spectroscopy (XPS) was detected to further clarify the electronic states of nanocomplexes formed by QCN and TQCN chelating free iron. , The high-resolution XPS spectra showed that the main peaks around 711.7 and 725 eV in the QCN/Fe 3+ nanocomplex and 712.5 and 725.3 eV in the TQCN/Fe 3+ nanocomplex were all assigned to Fe 2p 3/2 and Fe 2p 1/2 (Figure f,g and Figure S6), confirming the successful coordination of iron ions with QC molecules, not affected by TPP modification.…”
Section: Resultsmentioning
confidence: 63%
“…Subsequently, X-ray photoelectron spectroscopy (XPS) was detected to further clarify the electronic states of nanocomplexes formed by QCN and TQCN chelating free iron. 26,27 The high-resolution XPS spectra showed that the main peaks around 711.7 and 725 eV in the QCN/Fe 3+ nanocomplex and 712.5 and 725.3 eV in the TQCN/Fe 3+ nanocomplex were all assigned to Fe 2p 3/2 and Fe 2p 1/2 (Figure 2f,g and Figure S6), confirming the successful coordination of iron ions with QC molecules, not affected by TPP modification.…”
Section: Chelation-induced In Situmentioning
confidence: 74%
“…[7] Alternatively, active substrates, also named as micro/nanomotors (MNMs), are able to transport in solutions, making built-in solution mixing and a large portion cover. [8] They show enhanced mass transfer and collection range, leading to "on-the-fly" molecule enrichment with a significantly increased efficiency for enhanced metal-ion sequestration, [9] chemical and biological warfare agents detection and removal, [10] biomolecule recognition, [11] and so on. [12] For example, a magnetic "rod-like" micromotor doing continuous rotation under a rotating magnetic field can enhance the enrichment of trace R6G via creating a microvortex for efficient solution mixing.…”
Section: Introductionmentioning
confidence: 99%
“…Self-propelled nanomotors, with their ability to autonomously navigate and perform specific tasks on the nanoscale, have emerged as a fascinating area of research in recent years. These nanoscale devices harness various propulsion mechanisms, such as chemical reactions, light, magnetic field, and ultrasound, to generate motion. Self-propelled nanomotors offer unique advantages in addressing unmet challenges in biomedicine and the environment, showing great promise in targeted drug delivery, , sensing, , and environmental remediation, where their self-propulsion capabilities and small size (100 nm to 1 μm) enable them to actively navigate through complex biological or environmental matrices.…”
mentioning
confidence: 99%